Predicting mechanical properties of multiscale composites. (October 2013) - Kim, M; Okoli, O I; Jack, D; Park, Y-B; Liang, Z
Abstract : The effect of carbon nanotube (CNT) integration in polymer matrixes (two-phase) and fibre reinforced composites (three-phase) was studied. Simulations for CNT/polymer composites (nanocomposites) and CNT/fibre/polymer composites (multiscale) were carried out by combining micromechanical theories applied to nanoscale and woven fibre micromechanic theories. The mechanical properties (Young's modulus, Poisson's ratio and shear modulus) of a multiscale composite were predicted. The relationships between the mechanical properties of nano- and multiscale composite systems for various CNT aspect ratios were studied. A comparison was made between a multiscale system with CNTs infused throughout and one with nanotubes excluded from the fabric tows. The mechanical properties of the composites improved with increased CNT loading. The influence of CNT aspect ratio on the mechanical properties was more pronounced in the nanocomposites than in the multiscale composites. Composites with CNTs in the fibre strands generated more desirable mechanical properties than those with no CNTs in the fibre strands.